Myeloma: Patient accounts of their pathways to diagnosis - Howell, Debra A. (PLoS One, 2018)
BACKGROUND: Pathways to myeloma diagnosis can be prolonged, and are often preceded by multiple GP consultations and emergency presentation. This is the first qualitative study to examine events leading to diagnosis by asking patients about their experiences during this time. METHODS: Set within a UK population-based cohort, semi-structured interviews were conducted with 20 myeloma patients with varying characteristics and pathways, 12 of whom invited their relatives to take part. Interviews were audio-recorded and qualitative analysis undertaken. RESULTS: Pre-diagnostic awareness of myeloma was minimal. Disease onset was typically described as gradual, and health changes vague but progressive, with increasing loss of function. A wide range of symptoms was reported, with the similarity of these to self-limiting conditions failing to raise suspicion of myeloma among patients and GPs. Patients tended to normalise symptoms at first, although all eventually sought GP advice. GPs often initially suggested benign diagnoses, which were sometimes only revised after multiple consultations with persistent/worsening symptoms. Referrals were made to various hospital specialities, and haematology if associated with abnormal blood tests suggestive of myeloma. Once in secondary care, progress towards diagnosis was generally rapid. CONCLUSIONS: Accounts confirmed that pathways to diagnosis could be difficult, largely due to the way myeloma presents, and how symptoms are interpreted and managed by patients and GPs. Recognition of ‘normal’ health and consultation patterns for the individual could promote appropriate help-seeking and timely referral when changes occur, and may be more effective than raising awareness about the myriad of potential symptoms associated with this disease.